RITA-T (rapid interactive screening test for autism in toddlers): a scoping review of psychometric properties, cross-cultural validation, and clinical applications - Huijuan Liu; Guiju Zhang; Ziyun Li; Ting Zhang; Li Zhang; Yan Li (Frontiers in Psychiatry, 2026)
Background The Rapid Interactive Screening Test for Autism in Toddlers (RITA-T) is a clinician-administered, interactive screening instrument for toddlers aged 18–36 months that directly assesses core social-communicative abilities through structured play. Since its introduction in 2015, validation studies have emerged across diverse populations and cultural contexts. Objective This scoping review systematically maps the evidence on RITA-T’s development, psychometric properties, cross-cultural validation, clinical applications, and comparison with other level 2 screening instruments. Methods A systematic search of PubMed, Web of Science, Scopus, PsycINFO, and CNKI was conducted through June 2026. Studies reporting original data on RITA-T administration in toddlers aged 18–36 months were included. Methodological quality was assessed using the QUADAS-2 tool. Results Of 48 records identified, 10 original studies met the inclusion criteria: 7 diagnostic validation studies encompassing 659 toddlers across five countries (United States, Canada, Lebanon, Turkey, and China) and 3 implementation or training studies. RITA-T yielded strong psychometric properties across settings, with reported cutoff scores of 14–17, sensitivity of 0.74–1.00, and specificity of 0.50–1.00. Cross-cultural adaptations demonstrated comparable diagnostic accuracy across English, Arabic, Turkish, and Chinese versions. Conclusions RITA-T represents an effective level 2 ASD screening tool with robust cross-cultural applicability. Future research should address long-term predictive validity, telehealth adaptation, and cost-effectiveness.